Accuracy of Solar Eclipse Calculation Algorithm Based on Jet Propulsion Laboratory Data Nasa - Basthoni, M (Al-Ahkam, 2020)
DE200 and DE405 are Development Ephemeris (DE) series released by the National Aeronautics and Space Administration (NASA) in 1981 and 1997. NASA uses DE405 to predict solar eclipses in 2011-2020. While before 2011 and after 2020 NASA uses VSOP87/ELP200 theory-based DE200. Why NASA not only use more updated series DE405 and still use old release DE200? What is the difference of DE200Â  accuracy compared to DE405 to predict solar eclipse? This needs to be researched because the solar eclipse predicted by NASA is used as a reference by the researchers. To answer this question, this paper proposes a solar eclipse computation algorithm based on DE200 and DE405 data and the results will be compared with the results of observations of the March 9, 2016, solar eclipse that have been carried out langit selatan to find out a more accurate DE series. The results of this study indicate that the DE200 series is more accurate than DE405 with an average difference of 0.5 - 0.6 seconds with the results of observations.